Efektivitas Iklan Televisi Sabun Pembersih Muka di Kota Yogyakarta (Pendekatan Consumer Decision Model) - Albari Albari (Universitas Islam Indonesia, 2007)
Promotion via TV is believed to be effective for communicating advertising recall and information’s to consumers, but relatively high cost. This research is aim at examining the effectiveness of promotion via TV done by several facial soap producers: Biore, Ponds and Dove through Consumer Decision Model (DCM) perspective. From regression analysis we can find that advertising recall has positive affect to brand recognition, confidence, attitude and intention to buy; brand recognition has positive affect to consumer confidence and attitude; consumer confidence and attitude has positive affect to intention to buy; and confidence or attitude as intermediate variable to advertising recall and intention to buy. ANOVA analysis shows that there is a significant difference of consumer perception on advertising recall (Biore), brand recognition, and consumer attitude. There is no difference of intention to buy based on budged, age and consumer job. Keywords: promotion effectiveness, consumer decision model, consumer good